2018
DOI: 10.31557/apjcp.2018.19.11.3245
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Differential Expression of Apoptotic Markers in Rat Oral Mucosa

Abstract: Objective:This study tests the hypothesis that gingival tissue produces age-dependent activation of apoptotic markers.Methods:To address the hypothesis, a prospective experimental study was conducted on 20 adult male albino rats, which were divided into two groups. Group 1 comprised rats aged six months (weighing 150–200 g), and group 2 included old rats aged one year (weighing 250–300 g). Gingival tissue and buccal mucosa biopsy samples were obtained from both groups. Histological and immunohistochemical (Bax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…In this study, concomitant with our histological findings, we found a significant decrease in gene expression levels of the cell proliferation marker Ki-67 in aged control relative to adult control rats. This finding was in agreement with other researches (26,34,35) that demonstrated a significant decrease in epithelial proliferation and rate of tissue turnover with age. Our results also revealed that aged rats treated with licorice showed significant increase in Ki-67 expression compared to those untreated.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, concomitant with our histological findings, we found a significant decrease in gene expression levels of the cell proliferation marker Ki-67 in aged control relative to adult control rats. This finding was in agreement with other researches (26,34,35) that demonstrated a significant decrease in epithelial proliferation and rate of tissue turnover with age. Our results also revealed that aged rats treated with licorice showed significant increase in Ki-67 expression compared to those untreated.…”
Section: Discussionsupporting
confidence: 94%
“…Histomorphometrically, this decrease was statistically significant. A similar finding was previously reported by Elias (26) , who found that the buccal mucosa of 1-year-old rats had less epithelial thickness and that the cells of different layers appeared diminished and reduced in height than those of 6-month-old rats. Moreover, several other reported age-related cellular alterations in oral mucosa aligned with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Although the OCD group showed increased PedBE EAA compared to the controls in both models (Figure 7), the model fitted on PedBE EAA accounting for both chronological age and estimated BEC proportion showed an attenuated From infancy to mid-childhood, there was a reliable and significant decrease in estimated BEC proportion in cheek swabs. This may be explained by the oral epithelial morphological changes reported in studies in rodents, which showed increases in size along with reduced density, decreased mitotic activity, and decreased proliferation of oral epithelial cells with age 25,26 . However, the decrease in BEC proportion was accompanied by a reciprocal increase in estimated neutrophil proportion, with the estimated proportion of no other immune cell type showing an association with chronological age.…”
Section: Accounting For Estimated Bec Proportion When Calculating Ped...mentioning
confidence: 96%
“…The mucosa of the oral cavity is subject to age-related processes such as cellular aging and immunosenescence [3][4][5][6]. For some authors, increasing age, particularly above 60 years, should be considered to be a risk factor for the development of oral squamous cell carcinoma [3,7], although the exact role of aging in the carcinogenic process remains unknown.…”
Section: Introductionmentioning
confidence: 99%